Benzodiazepine modulation of homomeric GABAAρ1 receptors: Differential effects of diazepam and 40´-chlorodiazepam - Andrea Beltrán González (2014)
GABAA receptors (GABAARs) are ligand-gated ion channels that mediate inhibitory neurotransmission in the central nervous system (CNS). They are members of the Cys-loop receptor family and display marked structural and functional heterogeneity. Many GABAARs receptor subtypes are allosterically modulated by benzodiazepines (BDZs), which are drugs extensively used as anxiolytics, sedative-hypnotics and anticonvulsants. One high-affinity site and at least three additional low-affinity sites for BDZ recognition have been identified in several heteromeric and homomeric variants of the GABAARs (e.g.: alpha1-beta2-gamma2, alpha1beta2/3, beta3, etc.). However, the modulation of homomeric GABAArhoRs by BDZs was not previously revealed, and these receptors, for a long a time, were assumed to be fully insensitive to the actions of these drugs. In the present study, human homomeric GABAArho1 receptors were expressed in Xenopus oocytes and GABA-evoked responses electrophysiologically recorded in the presence or absence of BDZs. GABAArho1 receptor-mediated responses were modulated by diazepam and 4´-chlorodiazepam in the micromolar range, in a concentration-dependent, voltage-independent and reversible manner. Diazepam produced potentiating effects on GABA-evoked Cl(-) currents and 4´-Cl diazepam induced biphasic effects depending on the GABA concentration, whereas Ro15-4513 and alprazolam were negative modulators. BDZ actions were insensitive to flumazenil. Other BDZs showed negligible activity at equivalent experimental conditions. Our results suggest that GABAArho1 receptor function can be selectively and differentially modulated by BDZs.